Coupled three-dimensional analysis of the progressive tunnelling-induced damage to masonry buildings: is it always worth it?. (December 2021) - Amorosi, Angelo; Sangirardi, Marialuigia
Highlights: Advanced FE analyses allow to detect tunnelling-induced damage to masonry buildings. 3D simulations of the progressive excavation are necessary in skew configurations. 3D single-step simulations are sufficient in orthogonal configurations. Accuracy of the soil and masonry models should be comparable in SSI problems. Abstract: The development of urban mobility implies the construction of tunnels, often interacting with valuable masonry structures. It is thus necessary to develop rational and reliable procedures to estimate the potential excavation-induced damage, which imply the analysis of the related soil-structure interaction problem. Classical approaches to soil-structure interaction are often characterised by relatively simple schematisations for either one or both components of the problem, as, for example, springs for the soil or equivalent plates for the structure. Such simplified assumptions prove to be appropriate for conventional soil-foundation cases, while show all their limitations when tackling more complex problems, as those involving the excavation in the vicinity or beneath masonry structures. In such cases, the need for reliable prediction of the potential damage induced by construction activities on surface structures justifies the adoption of more advanced numerical approaches, based on realistic constitutive assumptions for both soil and masonry, together with an accurate modelling schematisation of the excavation process. This is what proposed in this paper, where a 3D Finite Element approach is adopted to realistically model the multidimensional and progressive nature of the excavation process, the strongly non-linear soil behaviour and the non-linear anisotropic response that characterises masonry structures, here included accounting for their 3D geometrical characteristics. All the analyses are carried out with reference to a sample masonry building founded on strip footings, interacting with a shallow tunnel in a typical London soil profile, already examined in the literature. Different configurations of the structure, considering the sole façade or the whole building, are examined. Also, different relative positions of the tunnel and the structure, in terms of skew angle and eccentricity, are considered. In all the analyses, the excavation is simulated either reproducing the whole three-dimensional advancement of the tunnel or through a simplified single-step analysis. A critical review of the deformation regimes and related plastic points patterns resulting from the different analyses point out in which cases it is necessary to accurately model the 3D tunnel advancement to detect the transient effects governing the onset of structural damage.